Uji Aktivitas Antiplasmodium Dari Isolat Kulit Batang Kayu Tammate (Lannea coromandelica Houtt. Merr.) Secara In-Vitro - Karlina Amir Tahir; Haeria Haeria; Alifia Putri Febriyanti; St. Chadijah; Nursalam Hamzah (Faculty of Pharmacy, Universitas Muslim Indonesia, 2020)
One of the main causes of death and a major public health problem is malaria. Some drug resistance and the limited number of effective drugs have given the community a sense of worry. This makes the discovery of new antimalarial compounds very necessary. Based on the results of exploration of natural materials, Javanese wood is one of the plants that is efficacious as an antimicrobial and is thought to be efficacious as antiplasmodium. This study was then conducted to find hexan and ethyl acetate isolates from the Java wood fraction (Lannea coromandelica Houtt. Merr.) Which effectively inhibited the development of Plasmodium falciparum in vitro. This research is a follow-up study from previous studies in testing the fraction of Javanese bark against antioxidant activity. The procedure starts from hexan and ethyl acetate isolates with five concentrations of 10 (µg / ml), 1 (µg / ml), 0.1 (µg / ml), 0.01 (µg / ml) and 0.001 (µg / ml) 3D7 strain of Plasmodium falciparum was measured based on the average percent resistance. The results of this study indicate that etil asetat isolate have IC50 2,727 µg/ml, its mean moderate activity as antiplasmodium. While hexan isolate have IC50 >10 µg/ml its mean not have or low antiplasmodium activity.